To study the effect of Cocos nucifera oil when incorporated into tissue conditioner on its tensile strength and antifungal activity: An in vitro study - Gayathri Krishnamoorthy; Aparna I Narayana; Prakash Yegneswaran Peralam; Dhanasekar Balkrishanan (The Journal of Indian Prosthodontic Society, 2019)
Aim: This study aims to test the tensile strength and growth of Candida albicans on Viscogel tissue conditioner when incorporated with coconut oil (CCO) and to compare its efficacy with other antifungal agents. Settings and Design: Evaluative - In-vitro study design. Materials and Methods: Fifty dumbbell-shaped samples (n = 10) of Viscogel tissue conditioner were fabricated according to ASTM standard and were classified into 5 groups (10% CCO, 30% w/w tea tree oil, 5% w/w fluconazole, 0.03% w/w silver nanoparticles, and plain tissue conditioner). These samples were compared and evaluated for their tensile strength. Further to test the antifungal activity, a total of 60 samples (n = 15) were fabricated, each group (n = 15) was further divided into three subgroups (n = 5), namely 24-h, 3-day, and 5-day period, which were inoculated in sabouraud dextrose agar plate to test for the growth of C. albicans. Statistical Analysis Used: Oneway ANOVA and post hoc Tukey honestly significant difference test. Results: 10% w/w CCO yielded a mean tensile strength of 20.06 as compared to the plain tissue conditioner which showed a mean tensile strength of 17.81. Similarly, 10% w/w CCO incorporated into Viscogel tissue conditioner showed a significant reduction in the colonization of C. albicans on the 5th day. Conclusions: 10% w/w of CCO when mixed with Viscogel tissue conditioner showed a significant reduction in the growth of C. albicans, and addition of the same increased the tensile strength of the tissue conditioner.